Correction: A facile and sensitive tetrabromobisphenol-A sensor based on biomimetic catalysis of a metal–organic framework: PCN-222(Fe). Issue 44 (7th November 2018) - Yu, Guangxia; Song, Xin; Zheng, Shijie; Zhao, Qiang; Yang, Danting; Zhao, Jinshun
Abstract : Correction for 'A facile and sensitive tetrabromobisphenol-A sensor based on biomimetic catalysis of a metal–organic framework: PCN-222(Fe)' by Guangxia Yu et al., Anal. Methods, 2018, 10, 4275–4281.